Xerostomia correlates with pain sensitivity in burning mouth syndrome patients - Hongsen Zhao; Shujun Ran; Wenqian Huo; Kang Gan; Wenlu Li (Scientific Reports)
Abstract Patients with burning mouth syndrome (BMS) often exhibit abnormal somatosensory function, and xerostomia is a common accompanying symptom. This study aimed to explore whether xerostomia is associated with pain sensitivity in patients with BMS. A total of 82 female patients with BMS were enrolled, including 55 with xerostomia. The pressure pain threshold (PPT) on the tongue was measured via a digital pressure algometer. Pain sensitivity was assessed via the Pain Sensitivity Questionnaire (PSQ). Whole saliva flow rates were measured. The severity of xerostomia was evaluated via the Summated Xerostomia Inventory (SXI). Descriptive statistics were performed, along with chi-square tests, Pearson correlation analyses, and multiple linear regression analyses. There were no significant differences in the PPT or stimulated saliva flow rates between BMS patients with and without xerostomia (112 ± 53 vs. 129 ± 57, p = 0.5837; 1.55 ± 0.73 vs. 1.64 ± 0.62, p = 0.5837, respectively). BMS patients with xerostomia had significantly higher PSQ-minor scores (4.55 ± 1.36 vs. 3.93 ± 1.11, p = 0.0432 < 0.05). PSQ-minor scores were correlated with the duration of xerostomia (β = 0.399, p = 0.003) but not with the severity of xerostomia. Xerostomia had different effects on the two pain sensitivity dimensions in patients with BMS: there was no significant change in the experimentally obtained pain threshold, while the self-assessed suprathreshold pain intensity increased.